THE CONSTRUCTION OF EFFECTIVE LEARNING ECOSYSTEMS IN OPEN AND DISTANCE LEARNING (ODL) UNIVERSITIES: TECHNOLOGIES, INSTITUTIONAL PREPAREDNESS, AND CHANGE - Sam O. Smah (Journal of Research and Innovation In Open and Distance Learning, 2023)
A critical analysis of digital learning ecosystems in ODL universities reveals increasing adoption and innovation of technologies in the process of delivering education across the world. Though proponents of traditional-based education argue that students experiencing learning through ODL systems are disengaged from the learning process and that teachers are equally disconnected from the learning process, with insufficient value placed on face-face teaching, pressures to assign overinflated grades, and incentives to teach content only, and not critical thinking skills, however, technology has the potential to alleviate many of the challenges. Moreover, some of the challenges are peculiar to some of the ODL education systems, especially universities in the developing world. Emerging digital resources and technologies hold promise to enrich and revitalize ODL university systems, give students a deserved learning experience, and better prepare students and teachers to face the 21st century. Every aspect of learning, such as grading, assessment, access to reading materials, learning platforms and environments/classrooms, simulations, etc. is covered by emerging connected workplace technologies. The paper discusses the underlining determinant factors, namely institutional-management preparedness, employee attitudes, institutional research and technological innovations, stakeholder engagement, power supply, bandwidth/broadband issues, funding, digital policy frameworks, and the overall responsiveness to change that global ODL competitiveness imposes. It concludes that institutional preparedness and national priorities drive the effective direction of the change that meets the requirements of ODL learning systems.